Surgical Treatment of Posterolateral Rotational Instability of the Elbow: a Systematic Review - M. A. Haj Hmaidi; F. L. Lazko; A. P. Prizov; N. V. Zagorodniy; E. A. Belyak; M. F. Lazko; V. A. Nechayev (Неотложная медицинская помощь)
Posterolateral rotational instability (PLRI) of the elbow joint can occur acutely as a result of dislocation of the bones of the forearm, and also be chronic, for example, after inadequate healing of a previous rupture of the lateral ligamentous complex, in particular the lateral ulnar collateral ligament (LUCL). It is necessary to take into account that, as a result of repeated microtraumas, persistent pain syndrome and recurrence of dislocation develop, which can lead to disability. We conducted a systematic review of the literature according to the protocol outlined in the PRISMA guidelines. From 1,903 publications, 11 studies were selected that met our criteria and assessed the results of treatment of 181 patients. The main reason for the development of PLRI was simple traumatic dislocation of the forearm bones (37.5%). Of the studies that assessed the elbow joint using the MEPS, 86.5% of patients had excellent or good results, with a mean MEBS score of 91 points. Before surgery, pain syndrome was present in 131 patients (87.3%) out of 150, and in the postoperative period it was observed in 55 (36.6%) out of 150 (p=0.01). The incidence of recurrent instability after surgery was observed in 6.6% of patients. A review of the literature on the problem of the elbow joint shows that this problem has not been fully studied, treatment strategies differ and should be performed based on the surgeon’s experience and available data, however, it has been proven that the key to the stability of the elbow joint is the LUCL, which requires its restoration through its refixation or plastic surgery.